Answers

2016-04-22T11:05:55+05:30
Consider the equation as p(x) = 2x3 + x2- 5x +2 and g1(X) = 1/2 , g2(x) = 1 and G3(x) = -2                                                                                                                      now put the x value in the p(x)                                                                                           p(x) = 2.( 1/2) 3 + ( 1/2)2 - 5 . 1/2 +2                                                                                     =  2.(1/8) 3 + ( 1/4) - 5 .1/2 +2                                                                                       =   5/2 . ( it is not a zero of the polynomial)                                                       now continue the same method in above two cases.                                                                                 
0